FMCG Industry Customer Segmentation for Cosmetic Product at PT. Paragon Technology and Innovation - Amanda Sri Nugroho; Andi Saputro; Fitra Alghifari Suhardi; Jerry Heikal (Syntax Idea)
Paragon Technology and Innovation is an Indonesian company within the Fast-Moving Consumer Goods (FMCG) industry that produces cosmetic products. PT Paragon is currently planning to develop new product and need understand further what product shall be prioritized to develop. Customer segmentation could be applied to give initial guide to determine which product to develop first. It is a process that divides customers into groups to find out the characteristics, behavior, or needs of customers for a product. Customer segmentation needs to be conducted because it can be used as supporting data to find out customer characteristics and determine effective and efficient marketing strategies for the company. Segmentation is one of the strategies to face business competition, to retain customers, and to assist management in developing marketing strategies to increase sales and company growth. The purpose of this study is to categorize the customers of PT Paragon Technology and Innovation products based on their characteristics. To determine customer segmentation can be done using the K-Means clustering algorithm. The clustering process is carried out by grouping PT Paragon's customer transaction history data in 2023 in November based on four categories, namely Face Care, Hair Care, Body Wash, and Make Up. The data is analyzed using IBM SPSS to determine the characteristics of each cluster. The population and samples used in the research were 79 and 52. The number of clusters used was 5, namely cluster 1 or struggling man customers, cluster 2 or beauty enthusiast customers, cluster 3 or forever young customers, cluster 4 or beauty careless casual customers and cluster 5 or luxtomer. The main cluster that provides shared value for PT Paragon Technology and Innovation consumers is cluster 2 or beauty enthusiast customers. The main category for shared value is the make up category, referring to the result, we recommend PT Paragon to mainly developa product following that category.